Decrease in ethanol fermentation time for Sato making by Rhizopus sp. and mixed cultures of yeasts (Thai) - Deesuth, Orawan; Samneing, Amornrat; Laopaiboon, Pattana; Wechgama, Kitipong; Laopaiboon, Lakkana (Asia-Pacific Journal of Science and Technology, 2017)
The fermentation time for Sato making by single and mixed cultures of yeasts was compared. Four Satos were produced as follows: Sato number 1 (using a single strain of yeast from the Samritmaankhong Co. Ltd. factory), and Sato numbers 2, 3 and 4 (using mixed yeasts between the factory yeast and Saccharomyces cerevisiae NP01, S. bayanas EC1118 or S. cerevisiae Sweden, respectively). The results showed that using mixed cultures in Sato number 2 could reduce fermentation time from 35 days to 32 days with ethanol concentration of 10% (v/v). When sensory evaluation of the 4 Satos and Siam Sato (produced by Samritmaankhong Co. Ltd.) was determined by preference test, there was no significant difference among the 5 Satos (p>0.05). Determination of chemical compositions of the 5 Satos indicated that they contained at least 26 chemical compounds i.e. 15 main volatile compounds, 7 acids, 3 sugars and glycerol. The main chemical compounds in the Satos were classified by principal component analysis (PCA) into 4 groups. However, each group did not influence the sensory characteristics.